EVALUASI ANALISIS EFEKTIFITAS COPY NASKAH DENGAN MENGGUNAKAN ANALYTIC HIERARCHICAL PROCESS - Akmaludin, Akmaludin (Jurnal Pilar Nusa Mandiri, 2012)
Progress in the field of business needs the support of the promotion, promotion measures can be done in various ways, one of which is measured in the areas of advertising, as outlined in a manuscript copy. There are a number of methods to evaluate the manuscript copy of which Direct Rating Method (DRM), EPIC Model and Customer Response Index (CRI). For an evaluation copy of the script there is a measurement method of comparison can be done with the Analytic Hierarchical Process (AHP). AHP is a method that is widely used in decision making and scientific part of the decision support system, known as Dicission Support System (DSS). In the discussion of this paper is intended to evaluate the effectiveness of each level, from the three models are used as a measure to assess the effectiveness of course seen the manuscript copy of each of the variables used. AHP didigunakan as advanced testing seen from some of the other variables if the data, formulation, design output, and transfer knowledge. At the end of the method will be seen each grade level of importance of each variable AHP. It describes the advantages in terms of where each model is used, so that the decision in the form of a score variable AHP can provide valuable information for anyone who will take measurements of the effectiveness of the manuscript copy. Acquisition synthesis analysis results obtained based on the priority level of 0.507 the top priority is DRM, second and third priorities respectively 0.327 and 0.166 for the EPIC models for CRI, this is becoming a final decision by the AHP process.